The music theory of Godfrey Winham - Blasius, Leslie David, 1955- (Princeton, New Jersey : Department of Music, Princeton University, 1997)
This book serves as an introduction to the work of Godfrey Winham, an influential figure in American music theory circles in the 1960s. Little published in his lifetime, Winham left behind, at his premature death in 1974, a massive collection of notes: correspondence, unfinished articles, sketches for books, etc. These notes were transcribed and deposited in the Special Collections of Firestone Library at Princeton University. They cover a fascinating range of subjects: exercises in analytical logic, thoughts on the construction of a formally consistent music theory, studies of particular p.
Godfrey Winham's conception of music theory -- Selected excerpts -- The contents of the Winham archive.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Winham, Godfrey; Winham, Godfrey -- Archives; Winham, Godfrey; Music theory -- History -- 20th century; Théorie musicale -- Histoire -- 20e siècle.; MUSIC -- Instruction & Study -- Theory; Music theory; 1900-1999; Archives; History